Hungarian Monitoring, 16 June 1988 . [Magyar rádiófigyelő], 1988. június 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Flawed Soviet policy decisions - Polish political reforms - Economic transformation in Czechoslovakia - Austria joins the Common Market - Schultz: Romania is the most oppressive state in Eastern Europe Domestic Affairs: - Police arrest opposition members - Ministerial council in session - Refugees from Transylvania - Young Communist League (KISZ) letter against Romanian policy of reducing number of villages - Géza Kótai on Hungarian renovation and foreign policy - Schools nationalized 40 years ago Külpolitika - A szovjet külpolitika hibás döntései - A lengyel politikai reformok - A gazdaság átalakítása Csehszlovákiában - Ausztria Közös Piaci belépése - Schultz: Románia a legelnyomóbb állam Kelet-Európában Belpolitika - Ellenzékiek rendőrségi előállítása - A minisztertanács ülése - Erdélyi menekültek ügye - A KISZ levele a román település-csökkentés politikája ellen - Kótai Géza a magyar megújulásról és külpolitikáról - 40 éve államosították az iskolákat